2016
DOI: 10.1589/jpts.28.2581
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the back school program for the performance of activities of daily living in users of a basic health unit in Porto Alegre, Brazil

Abstract: [Purpose] Primary care is considered the gateway to the Brazilian public health system and is responsible for managing the most prevalent problems in the population. In this study, the effects of Back School on pain, functionality, and the performance of activities of daily living (ADL) in users with chronic musculoskeletal pain were evaluated. [Subjects and Methods] Forty-four users (33 females and 11 males) participated in Back School, with five two-hour theoretical and practical meetings held once a week. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…The results of systematic review indicated that due to the low- to very low quality of the evidence for all treatment comparisons, outcomes, and follow-up periods of Back School program for chronic nonspecific LBP, it is recommended that additional and future research be done to determine the different effects of this program ( Parreira et al, 2017 ). According to other studies report, the educational intervention and preventive program such as Back School program can be significantly effective in pain relief ( Glomsrød et al, 2001 ; Járomi et al, 2018 ; Van Hoof et al, 2018 ), increased the number of properly techniques in patient lifting ( Járomi et al, 2018 ) in nurses and decreased pain intensity ( Bartz et al, 2016 ) and disability ( Sahin et al, 2011 ), improved functionality, and the recovery of activities of daily living in people with chronic musculoskeletal pain ( Bartz et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of systematic review indicated that due to the low- to very low quality of the evidence for all treatment comparisons, outcomes, and follow-up periods of Back School program for chronic nonspecific LBP, it is recommended that additional and future research be done to determine the different effects of this program ( Parreira et al, 2017 ). According to other studies report, the educational intervention and preventive program such as Back School program can be significantly effective in pain relief ( Glomsrød et al, 2001 ; Járomi et al, 2018 ; Van Hoof et al, 2018 ), increased the number of properly techniques in patient lifting ( Járomi et al, 2018 ) in nurses and decreased pain intensity ( Bartz et al, 2016 ) and disability ( Sahin et al, 2011 ), improved functionality, and the recovery of activities of daily living in people with chronic musculoskeletal pain ( Bartz et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The comprehensive multidisciplinary programs Swedish Back School was introduced by Zachrisson Forsell in 1969 that aims to reduce the back pain and injury, teach people to care for their own backs and back pain in an active way to improve the functionality and quality of life. This program consisted of information on the structure and function of the spine, biomechanics, optimal posture, ergonomics, and performing special back exercises ( Bartz et al, 2016 ; Forssell, 1981 ; Straube et al, 2016 ). It helps nurses on how to protect the spinal structures in daily activities and work ( Brox et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…A metodologia das Escolas Posturais é uma abordagem de educação em saúde bastante utilizada em pesquisas direcionadas a escolares 22 e indivíduos adultos e idosos com dores musculoesqueléticas 10,[23][24] . Entretanto, não foram encontrados estudos que avaliaram os efeitos de um programa de Escola Postural destinado especificamente à população idosa saudável, bem como para idosos que praticam exercícios físicos regularmente.…”
Section: Discussionunclassified
“…The times evaluated in the study were: 3, 6, 9, 12, and 15 min. These different moments were used to minimize the potential loss of spontaneity of the studied population when being filmed [14,15].…”
Section: Methodsmentioning
confidence: 99%